Adaptive time‐varying formation control for teleoperation system: A finite‐time approach. (16th December 2022) - Su, Shan; Ji, Yude
Summary: In this article, the finite‐time formation control scheme is put forward for teleoperation system with time delay. First, a group of finite‐time observers are established to address the teleoperation system with time‐varying delay issue and via linearly parameterize to deal with the uncertainty in the system. The theory of self‐stable domain (SSR) is then applied to provide sufficient circumstances for the observers error dynamics to converge in finite‐time. Then, in line with the estimation of time delay derivatives to reconstruct the regression matrix as well as the adaptive law, the observer based time‐varying formation control protocol is drawn up. On the basis of finite‐time state‐independent input‐to‐output practical stable (FTSIIOpS) theorem, sufficient conditions for teleoperation implement time‐varying formation are developed. Finally, simulation is being used to validate the efficiency of the proposed strategy.